Zugänge zur Rechtssemantik: interdisziplinäre Ansätze im Zeitalter der Mediatisierung - Vogel, Friedemann (Linguae & litterae, 2015)
"How do we appropriately analyze the development of meaning in the law in an age of medialization? In this volume, experts from in linguistics, the media sciences, legal studies, and computer science examine this question in the context of jurisprudence, legislation, and legal scholarship. They describe qualitative and computer-assisted approaches to legal semantics to make a reflective contribution to juristic methodology and legal theory" --
Keywords: Aufsatzsammlung; Semantik; Rechtssprache